3-D analysis of one-strut failure in braced excavation - Tan, Pei Qi. (2012)
In this project both 2D and 3D finite element analysis, using PLAXIS 2D and 3D, were carried out for excavations in soft clay. For the 3D analysis, the length of excavation was slightly more than four times the excavation width. Walls with various bending stiffness were considered. The strut failure level was designated at either the 3rd layer or the 5th layer, in a 5 layer strutting system. The shear strength of the deeper clay layer was varied for better understanding of the excavation site.Comparing the data from the three-dimensional analysis, the plane strain analysis resulted in a slight overestimation of the results. Generally, the stiffer wall resulted in smaller lateral wall displacements.Embedding the wall in a stronger clay layer resulted in smaller lateral wall displacements and smaller strut loadings. The plane strain and three-dimensional analysis indicates that failure of the lowest strut is generally more critical than failure of a middle strut. The redistribution of strut loadings were studied, however, the fluctuations of results concluded no general trend of this part of the study.